2003
DOI: 10.1073/pnas.1834198100
|View full text |Cite
|
Sign up to set email alerts
|

Little evidence of bone marrow-derived hepatocytes in the replacement of injured liver

Abstract: We have tested the ability of bone marrow (BM) cells (BMCs) to form hepatocytes in liver injury models. We used three models: T here have been a number of reports that show the potential of adult rodent bone marrow (BM) cells (BMCs) to transdifferentiate into a variety of cell types (1-7), including hepatocytes (8 -10). One of the best examples for the transdifferentiation has been the ability of BM-derived hapatocytes to repopulate the liver of mice with fumarylacetoacetate hydrolase knockout mouse (FAHϪ͞Ϫ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(90 citation statements)
references
References 21 publications
6
84
0
Order By: Relevance
“…Bone marrow-derived hepatocytes may originate from the mesenchymal compartment, rather than the hematopoietic compartment [22] . However, other data demonstrate that bone marrow-derived hepatocyte is only a possible but rare event, even in the presence of very strong selection pressure [23] . Several reports have demonstrated that cell fusion is the principal source of bone marrow-derived hepatocytes [24] , and bone marrow-derived hepatocytes are primarily of mature myelomonocytic cells which fuse spontaneously with host hepatocytes producing functional liver repopulation [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow-derived hepatocytes may originate from the mesenchymal compartment, rather than the hematopoietic compartment [22] . However, other data demonstrate that bone marrow-derived hepatocyte is only a possible but rare event, even in the presence of very strong selection pressure [23] . Several reports have demonstrated that cell fusion is the principal source of bone marrow-derived hepatocytes [24] , and bone marrow-derived hepatocytes are primarily of mature myelomonocytic cells which fuse spontaneously with host hepatocytes producing functional liver repopulation [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Detection of y chromosomes was performed on 6-m cryostat sections, using a mouse Y chromosome-specific FITC-labeled probe (Starfish; Cambio, Cambridge, UK) following the procedure described by Kanazawa et al (10). Sections then were washed according to the manufacturer's instructions.…”
Section: Y Chromosome Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…[1][2][3][4]7,21,22 In the present study, no relationship between tissue injury due to either conditioning regimen or the extent of GVHD and the presence and proportion of donor-derived hepatocyte and gastrointestinal epithelial cell repopulation was observed, although the proportion of donor-derived hepatocyte and gastrointestinal epithelial cell repopulation in individuals with severe GVHD was slightly greater. Kanazawa et al 23 and Korbling et al 7 reported that the frequency of DDHR in recipients is unrelated to liver injury in both experimental models and humans. In contrast, Theise et al 1 reported that the extent of engraftment in sex-mismatched graft seems to correlate with the severity of tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Basic concepts on stem cell biology including plasticity, transdifferentiation and fusion have all been reported. 1,2,5,[22][23][24][25][26][27][28][29] Recent progresses in stem cell studies have indicated that certain mammalian cells maintain a high degree of plasticity for multilineage cell differentiation. 25,26 The plasticity is supported by the finding of intrahepatic chimerism in transplant recipients.…”
Section: P=009mentioning
confidence: 99%